Cost-effectiveness analysis of current non-mandatory hepatitis B vaccination coverage vs expanding coverage among healthcare workers in Ethiopia - Dinksew Tewuhibo; Getahun Asmamaw; Wondim Ayenew (Taylor & Francis Group, 2022)
Background Ethiopia is a country with high endemicity in Hepatitis B (HepB) virus infection. However, only 14% of healthcare workers (HCWs) are currently immunized via a non-mandatory strategy in the country. Hence, this study aimed to estimate the cost-effectiveness of the current vaccination coverage and increasing coverage among HCWs in Ethiopia. Methods Based on current practice, the study considered a monovalent HepB vaccine, which has a 90% protection rate with a complete three-dose series for lifelong protection. Markov model for current coverage (14%) and expanding vaccination coverage to 80% (as per World Health Organization (WHO) recommendation) was simulated based on the data got from both primary and secondary data. Secondary data, particularly cost and effectiveness data, were gained from published articles, WHO guidelines, and Ethiopian Federal Ministry of Health documents. Cost-related data for vaccination and chronic HepB treatment were also gathered by interviewing expertise from Tikur Anbesa specialized hospital. We conducted the study from a healthcare payer perspective, with a 3% discount rate of cost and health outcome as recommended by the WHO. The primary health outcome was measured by the Incremental Cost-Effectiveness Ratio (ICER). We employed deterministic analysis and tornado diagrams to manage parameter uncertainty and show a plausible range of cost and effectiveness of variables. Results Current vaccination program is more expensive (USD 29.99) with a more additional cost of USD 1.32 and with reduced effectiveness of 0.08 Life Years (LYs) compared to the expanded HepB vaccination strategy which costs USD 28.67 and gives a relatively high total LY gain of 28.62. The resulting ICER was USD-16.23 per LYs gained. The negative ICER shows that the expanded HepB vaccination strategy dominated the current vaccination strategy. A one-way sensitivity analysis also revealed that the current vaccine coverage was dominated by an increase in the risk of infection among unvaccinated individuals. Conclusions Expanded vaccination coverage (to 80%) was found the most cost-effective strategy in Ethiopian HCWs compared to the current non-mandatory vaccine coverage (14%). In addition, the results of one-way and two-way sensitivity analysis reveal the robustness of our model conclusion.